1980
DOI: 10.1007/bf01875375
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of glycine froml-alanylglycine into renal brush border vesicles

Abstract: Isolated renal brush border microvilli vesicles were employed to study the uptake of radiolabel from L-Ala. [3H]Gly and D-Ala.[3H]Gly as well as to determine the presence of dipeptidase activity. Microvilli vesicles were prepared from porcine kidney cortex by differential centrifugation through hypotonic Tris buffer containing Mg2+. The microvilli vesicles transiently accumulated radiolabel from L-Ala. [3H]Gly to higher levels than were initially present in the incubation medium (overshoot phenomenon). This ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Welch and Campbell (14) suggested that the enzyme might play a role in retaining essential amino acids by hydrolyzing filtered dipeptides that would otherwise be excreted in the urine. The effects of enzyme inhibition by cilastatin on neonatal homeostasis are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Welch and Campbell (14) suggested that the enzyme might play a role in retaining essential amino acids by hydrolyzing filtered dipeptides that would otherwise be excreted in the urine. The effects of enzyme inhibition by cilastatin on neonatal homeostasis are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MDP has been implicated in the metabolism of Cys-Gly and the X-CG, leukotriene D 4 (LTD 4 ) (Adachi et al, 1989). The enzyme is found in the renal brush border microvillar membrane and also in the lung (Brewis et al, 1994;Campbell et al, 1990;Curthoys et al, 1980;Welch and Campbell, 1980). In pig kidney, immunohistochemical analysis revealed that MDP is present in the cortex but not in the medulla (Littlewood et al, 1989).…”
Section: Cys-gly Conjugate Hydrolysismentioning
confidence: 99%
“…RDPase is a zinc-metalloenzyme principally localized in the brushborder of the renal proximal tubule (Welch and Campbell, 1980), but is also found with high activity in other tissues such as the lung, pancreas, testis and intestinal mucosa (Campbell et al, 1990;Kera et al, 1999). Dipeptidase activity was also detected in the urine of human, where it was named as urinary dipeptidase (Udpase), and was subsequently purified from human urine (Park et al, 1992).…”
mentioning
confidence: 99%
“…RDPase and Udpase were identified as the same enzyme on the basis of various physicochemical characteristics such as substrate specificity, immunoreactivity and amino acid sequence identity (We et al, 1997). Various physiological role of this enzyme has been suggested such as hydrolysis of dipeptides for reabsorption in the kidney (Welch and Campbell, 1980), *To whom correspondence should be addressed. Tel: 82-62-530-2923, Fax: 82-62-530-2949 and metabolism of glutathione and leukotriene D4 (Campbell et al, 1990).…”
mentioning
confidence: 99%